(untitled) (Al-Qamar, 2025)
Caregivers of individuals with substance use disorders (SUDs) in Pakistan encounter a range of emotional, financial, and social challenges that vary significantly across provinces due to differences in healthcare infrastructure, cultural norms, and socioeconomic conditions. This study aimed to conduct a cross-provincial comparison of the challenges faced by caregivers of adults undergoing treatment for SUDs in Pakistan. A qualitative research design was employed using non-probability sampling. A total of 48 caregivers from four provinces (Punjab, Sindh, Khyber Pakhtunkhwa, and Baluchistan) participated in semi-structured interviews. Data were collected till data saturation point. Five major themes emerged: emotional and psychological stress, financial burden, access to healthcare facilities, stigma and social isolation, and coping strategies. Caregivers in Khyber Pakhtunkhwa and Baluchistan reported significantly higher emotional distress, stigma, and financial strain due to limited access to mental health services and treatment centers. In contrast, caregivers in urban areas of Punjab and Sindh experienced better support systems but still faced challenges in rural regions. The findings highlight profound regional disparities in the caregiving experience across Pakistan, emphasizing the urgent need for culturally sensitive, region-specific interventions.